The Legal Responsibilities of A Notary as A General Official for Authentic Deeds related to the Criminal Action of Forgery - Heriyanti, Heriyanti; Pakpahan, Emir Syarif Fatahillah; Jeriko Tumanggor, Togap (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
The Notary's Code of Ethics is a guideline for the attitude and behavior of a notary. It is necessary to maintain the quality of legal services to the public. In carrying out his duty, aside from referring to the Law of Notary, a Notary must also obey and act in accordance with the moral principles of notary practice in Indonesia. The supervision of notaries by the Notary Supervisory Board is to ensure that notaries always act in accordance with the legal principles that underlie their authority and can avoid abuse of the authority or trust given. This empirical research aims to determine the number of public complaints received by the Regional Notary Supervisory Council in Medan regarding alleged violations of the ethics code committed by Notaries, the effectiveness of supervision implementation and prevention of violations of the Notary ethics code by the Notary Supervisory Council during the last 4 (four) years of from 2018 to 2021. The research results of this study show that in 2018 there were 8 (eight) complaints, in 2019 there were 12 (twelve) complaints, in 2020 there were 24 (twenty four), and in 2021 there were 10 (ten). Notary Supervision by the Notary Supervisory Council is based on Law No. 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning the Position of Notary, Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number: M.02.PR.08.10 of 2004, Ministerial Decree Law and Human Rights of the Republic of Indonesia Number M.39-PW.07.10. 2004 and the role of the Regional Supervisory Board includes preventive purposes, namely reflecting on the position of the Notary Ethics Code in order to provide material related to the implementation of the position of Notary, participating in seminars, and checking Notary protocols.